2006
DOI: 10.1097/01.acm.0000225219.53325.52
|View full text |Cite
|
Sign up to set email alerts
|

Using the Tool for Assessing Cultural Competence Training (TACCT) to Measure Faculty and Medical Student Perceptions of Cultural Competence Instruction in the First Three Years of the Curriculum

Abstract: Faculty and third-year students at one medical school responded congruently about the relative degree to which cultural competence instruction occurred. The TACCT can be used to identify significant gaps in cultural competence training and inform curricular revision. Further studies involving other schools are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 11 publications
2
37
0
7
Order By: Relevance
“…Although various model curricula have been proposed (Box 2) these have, so far, not been incorporated into directives from the various UK professional training bodies. [10][11][12][13] In fact, the motivation for establishing cultural diversity training cited by most educational leads lay in centres' own appreciation of cultural-specific healthcare needs, rather than because of heeding guidelines from professional bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various model curricula have been proposed (Box 2) these have, so far, not been incorporated into directives from the various UK professional training bodies. [10][11][12][13] In fact, the motivation for establishing cultural diversity training cited by most educational leads lay in centres' own appreciation of cultural-specific healthcare needs, rather than because of heeding guidelines from professional bodies.…”
Section: Discussionmentioning
confidence: 99%
“…8 In order for medical education to meet the goal of improving healthcare for the whole population, training needs to incorporate the principle of individualising care, including recognising the specific health needs, values and communication issues of ethnic minorities. [9][10][11][12][13] Although UK healthcare professional training bodies in medicine, nursing, physiotherapy, occupational therapy, speech and language therapy and pharmacy have all issued general guidelines that encourage equality and diversity appreciation in educational curricula, 14 there are currently no requirements for teaching centres to provide formal cultural diversity training. In this study the nationwide frequency, characteristics and motivations for formal cultural diversity teaching for the main types of UK healthcare professionals are documented.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the schools emphasized specific cultural information about the ethnic communities they served and general themes, such as the doctor-patient relationship, socioeconomic status, and racism 30 . A more recent assessment of curriculum content at seven U.S. medical schools funded to develop cultural competency/health disparities curricula found that topics on health disparities, community partnerships, and bias/stereotyping topics were the least likely to be presented 31 .…”
Section: United Statesmentioning
confidence: 99%
“…Seven of the 18 PI respondents reported collaborating on Association of American Medical College products related to health disparities education (e.g., Tool for Assessing Cultural Competence Training or TACCT) [14][15][16][17][18][19] , participated in expert literature review panels, and/or created Liaison Committee on Medical Education (LCME) faculty and student admission statements of diversity. One PI respondent reported working with the National Board of Medical Examiners to include cultural competency and health belief questions in the USMLE Step 3 Board examination.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the 18 Consortium PIs developed videos or other educational tools available in MedEdPORTAL 17,18,[22][23][24][25][26][27][28][29] . Assessment tools or performance checklists were developed, modified or validated by 13 Consortium members including those published in the peer-reviewed literature 16,18,30 . Standardized patient (SP) formative and evaluative cases were implemented by ten Consortium PIs.…”
Section: Examples Of Curricular Products and Dissemination (From Respmentioning
confidence: 99%